2004
DOI: 10.1016/j.bone.2004.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 enhances alveolar bone formation in the rat mandible

Abstract: Prostaglandin E 2 (PGE 2 ) induces bone formation in stress-bearing bones. The mandible, a stress-bearing bone, is loaded daily during mastication. The aim of this study was to determine if PGE 2 delivered locally to the mandible over 20 days enhances alveolar bone deposition. In 18 Lewis rats, controlled-release pellets containing PGE 2 were implanted on the buccal aspect on the left-hand side of the mandible, mesial to the root of the first molar. Controlled-release pellets locally delivered 0.1, 0.05, or 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…In addition, the species of subject may influence responses to prostaglandin E 2 (22). Our findings are consistent with a recent study which showed that locally applied prostaglandin E 2 could enhance the rate of bone formation in a rat mandible (24). Another possibility is that while this drug suppresses the inflammation, it may concurrently stimulate bone resorption in a manner similar to that proposed for cyclooxygenase‐2 inhibitors in rheumatoid arthritis (25).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the species of subject may influence responses to prostaglandin E 2 (22). Our findings are consistent with a recent study which showed that locally applied prostaglandin E 2 could enhance the rate of bone formation in a rat mandible (24). Another possibility is that while this drug suppresses the inflammation, it may concurrently stimulate bone resorption in a manner similar to that proposed for cyclooxygenase‐2 inhibitors in rheumatoid arthritis (25).…”
Section: Discussionsupporting
confidence: 94%
“…The labeling lines of tetracycline and calcein were not detected in the low‐mineralized bone area in this study. In general, these fluorescent lines are known to be clearly visible in mature bone (24). Our results may indicate that newly formed alveolar bone is still immature and the rough surface is one phenotype showing such immaturity.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that compressive forces induce the expression of pro‐inflammatory mediators and that interleukin‐1β has been implicated as one of the major cytokines synthesized in response to compressive forces applied on the PDL (6,26–28). Interleukin‐1β stimulates PGE 2 synthesis, which is essential to induce an osteogenic response during bone resorption and formation (14,29).…”
Section: Discussionmentioning
confidence: 99%